Detection of Cryptococcus sp. from clinical and subclinical mastitis in dairy cows and assessment antifungal activity to fluconazole, amphotericin B, and nystatin - Kadhim, Mahmood Ahmed (Diyala Journal for Veterinary Sciences, 2023)
Cryptococcus species are increasingly recognized as significant pathogens causing mastitis in dairy cows. The objective of this research was to detect Cryptococcus spp. in milk samples collected from cows with subclinical and clinical mastitis. Additionally, assessment antifungal activity to fluconazole, amphotericin B, and nystatin. Milk samples were collected randomly from various locations in Diyala province and a total of 27 samples were obtained. Each sample was cultured on Sabouraud Dextrose Agar (SDA) and the resulting isolates were identified using various laboratory methods such as morphological and microscopic examination. Of the 27 samples, 8 (28.6%) were positive for Cryptococcus species, including Cryptococcus neoformans (5 samples, 62.5%), Cryptococcus gattii (2 samples, 25%), and Cryptococcus laurentii (1 sample, 12.5%), as determined by Cryptococcus differential agar (CDA). Antifungal susceptibility examination was performed using disk diffusion method and all 8 isolates were found to be 100% resistant to all examined medications in this study; fluconazole, amphotericin B, and nystatin.